Short term results of modular bipolar hemiarthroplasty for the treatment of neglected trochanteric femur fracture in the elderly - Bhat, Towseef Ahmad; Ali, Zameer; Sehgal, Manik (International Journal of Research in Orthopaedics, 2019)
Background: In rural India because of native practitioner culture people tend to neglect orthopaedic injuries and often present late to the hospitals. Bipolar hemiarthroplasty for neglected intertrochanteric fractures of the femur in the elderly yields good clinical results in terms of early postoperative ambulation. This will have a direct effect on the general condition and postoperative rehabilitation. Methods: Sixteen patients with proximal extracapsular femoral fractures presented average 10.4 weeks late from the day of injury, were treated with modular bipolar hemiarthroplasty. There were 11 men and 5 women, with mean age of 72.8 years (range: 65–83 years). Primary cemented bipolar hemiarthroplasty was performed using the Hardinge lateral approach in a lateral decubitus position. Harris hip score was used for the clinical evaluation of the patients. Results: Clinically, the Harris hip score at the last follow-up ranged from 92 to 59, with a mean value of 81.7. Postoperative radiographs showed a good position in all patients. 1 patient developed complication during cementing and 1 case came with dislocation. No case of infection, acetabular erosion, periprostheic fracture or implant loosening was reported in this study. Conclusions: Primary cemented bipolar hemiarthroplasty is a good choice in elderly patients with neglected intertrochanteric fractures of the femur.